Pengaruh Financial Literacy dan Penggunaan Digital Payment (QRIS) Terhadap Kinerja UMKM (Studi UMKM Sektor Makanan dan Minuman di Kecamatan Tuah Madani Kota Pekanbaru - Syifa Sakinah; Ruzikna Ruzikna (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economy but still face challenges in improving their business performance. Different levels of financial literacy influence the ability of business owners to make appropriate financial decisions. In addition, the use of digital payments such as QRIS not only facilitates transactions but also supports financial record-keeping, improves operational efficiency, and expands market access. These factors are considered to contribute to the improvement of MSME performance.This study aims to determine and analyze the effect of financial literacy and the use of digital payment (QRIS) on the performance of MSMEs in the food and beverage sector in Tuah Madani District, Pekanbaru City. This research employs a quantitative method. The sample consists of 91 MSMEs selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using inferential statistics using SPSS version 22.The results show that financial literacy and the use of digital payment (QRIS) have a significant effect on the performance of MSMEs in the food and beverage sector in Tuah Madani District, Pekanbaru City